Feeling the Joy of Life in the Body: Ludic Activities in the Bioenergetic Analysis with Children - Dantas, Périsson (Bioenergetic Analysis, 2024)
The article aims to present how Bioenergetic Analysis exercises can be applied in a playful way in Child Psychotherapy. There are specificities in handling body work with children, which are: a) the understanding that patients are still in the process of ego development; b) plasticity of armor formation in this phase; c) the intention to strengthen more adaptive defense systems. As an initial theoretical review, the pioneering initiatives of body psychotherapies on child clinical psychology are discussed and a proposal for the use of bioenergetic exercises is launched, following the assumptions for the energetic mobilization of the armor rings in children, in the bottom-up sense. Finally, this article justifies the importance of training psychotherapists for specific care with children as a way of promoting health and rescuing Reich’s intention to prevent neuroses.